DAYA TERIMA BOLU LAPIS KOJO UBI JALAR KUNING SEBAGAI SNACK RENDAH KALORI DAN PENAMBAH SERAT - RA Febi; Eliza Eliza; Hana Yuniarti; Sriwiyanti Sriwiyanti; Sartono Sartono (JGK:Jurnal Gizi dan Kesehatan, 2021)
Background: Obesity was defined as abnormal or excessive fat accumulation that can impair health. One strategy to overcome the problem of obesity was to provide low-calorie foods. One of the local foods that can be used as a low-calorie meal and fiber enhancers was the yellow sweet potato cake with kojo layer. The purpose:This study aims to determine the best formulation of yellow sweet potato cake with kojo layer. Methods: This study used an experimental design with a non-factorial completely randomized design (CRD). The ingredients used were yellow sweet potato, wheat flour, eggs, stevia sugar, salt, margarine, and low-fat milk Results: The results showed that the selected yellow sweet potato cake with kojo layer with F2 treatment (60% addition of yellow sweet potato) with a total energy content of 197.39 Kcal, 13.55% protein, 2.11% fat, 31.05% carbohydrate (per 100 grams). Conclusion: Yellow sweet potato kojo layer sponge can be used as a low -calorie food alternative and fiber enhancers.